Perancangan Rekam Medis Berbasis Web Pada Praktek Umum Dokter Adrianus Riyanto - Elisabeth, Elisabeth (TEMATIKA, Journal of Informatics and Information Systems, 2013)
Along with the development of technological information nowadays, and many problems that occur at The General Practitioner Doctor Adrianus Riyantoâ€™s Practice so the medical records data which used to be recorded by conventional way finally are grown into an application that is called medical records application. This application was started by analyzing the problem by interviewing the doctor, nurse, and Â patient. This aplication was built by Hypertext Preprocessor language and MySQL which the output will be implemented and tested by interview process. The reachable result indicates that medical records development assist to improve productivity and efficiency work from general practitioner.